2020
DOI: 10.1021/acs.jpca.0c02912
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Solution-Processed Mesoporous WO3 as an Interfacial Cathode Buffer Layer for Photovoltaic Applications

Abstract: Dextran-templating hydrothermal synthesis of monoclinic WO3 exhibits excellent specific surface area of ∼110 m2/g and a monomodal pore distribution with an average pore diameter of ∼20 nm. Dextran plays a crucial role in generating porosity on WO3. The role of supporting dextran has been investigated and found to be crucial to tune the surface area, porosity, and morphology. The photoluminescence and X-ray photoelectron spectroscopy studies reveal the existence of oxygen vacancies in substoichiometric WO3, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 73 publications
(110 reference statements)
1
14
0
Order By: Relevance
“…R rec is charge transfer resistance at the perovskite/carbon interface. 59 In Fig. 5d, the large parabola in the high-frequency region implies higher transportation and exchange resistance from perovskite to carbon counter electrode, which will influence the fill factor as reflected from J-V characterization.…”
Section: Photovoltaic Performance Of C-pscs For S T and T T Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…R rec is charge transfer resistance at the perovskite/carbon interface. 59 In Fig. 5d, the large parabola in the high-frequency region implies higher transportation and exchange resistance from perovskite to carbon counter electrode, which will influence the fill factor as reflected from J-V characterization.…”
Section: Photovoltaic Performance Of C-pscs For S T and T T Conditionsmentioning
confidence: 99%
“…influence of surrounding moisture and air, although the devices were kept inside a chamber of fixed temperature. It was suggested that excess PbI 2 in MAPbI 3 could help to passivate defects at surfaces, and grain boundaries and a small amount of residual PbI 2 in perovskite supports to reduce charge recombination and improves the V OC and FF 59. As a result, the devices do not lose its V OC under thermal stress, indicating the PCE loss is mainly restricted with the J SC .…”
mentioning
confidence: 99%
“…The porous WO 3 boosted the J sc of perovskite cells to 24.21 mA cm À 2 which is higher than that of nonporous WO 3 (20.15 mA cm À 2 ). [67] A combination of photochemical and electrochemical properties of WO 3 makes it an efficient photoelectrochemical catalyst. These catalysts use photons to excite surface molecules that are then used in a reaction that generates energy.…”
Section: Photo-/electrocatalystmentioning
confidence: 99%
“…An effort has been executed to find a suitable medium between high electrical efficiency and a high AVT, as shown in Figure 5. The thickness and structure of the mesoporous layer create an impact on PSC performance [150]. The optical transparency of the other interlayers and the semi-transparent electrode of PSC influence to archive high PCE [151].…”
Section: Transparency and Efficiency Tradeoff Of Pscsmentioning
confidence: 99%